(3TQM GdhGajIs - (3GdCYQLj, GdMSjfj, GdcGXej, eMSf Hf MSf Hf GdeQJVi, J(B1227(3g`s ((3eMeO Ydj Hf eMeO HGbQ GdCUagGfjs)
(3ChdgG (B:s
(3GdMeO ddg GdhGgH GdefGf eJHY GdEMSGf HGdEMSGf(B...(3CeG HYO ajbhd GdYHO GdabjQ(B...(3deG cGf eOQc GdCMcGe GdTQYjI aj GdcJGH GdeLjO hGdSfI GdZQGA(B...s
(3BNQgG (B:s
...(3hef GdfGS ef jQi GdYHhOjI eGfYG ef GdbHhd EPG cGfJ Ydi Gdehdi hcGdePchQI ajeG YOG eG JbHd ajg TgGOI GdfSGA(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B286s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs